2019
DOI: 10.1002/jcb.29369
|View full text |Cite
|
Sign up to set email alerts
|

ShRNA‐mediated matrix metalloproteinase‐2 gene silencing protects normal cells and sensitizes cancer cells against ionizing‐radiation induced damage

Abstract: Introduction Ionizing radiation (IR) affects healthy tissues during the treatment of cancer radiation therapy and other nuclear and radiological accidents. Some natural compounds showed nonspecific radioprotective activity with severe side effects. The present study is aimed to develop potent and specific radioprotective short hairpin RNA (shRNA), which selectively protects normal cells from IR by specifically targeting matrix metalloproteinases (MMP‐2). Results IR reduced the viability of human normal dermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 105 publications
1
2
0
Order By: Relevance
“…Silencing of Ku70 transcription and translation is known to be more significant than the mitigation of Ku70 acetylation modifications, indicating a Ku70 dosage-dependent elevation of Bax in cells (Ding et al 2021;Wang et al 2020). The Bax then leads to the release of pro-apototic factors, such as Cyt-c from the mitochondria and the activation of the caspases, resulting in the initiation of the intrinsic pathway of apoptosis (Shailender et al 2020;Wang et al 2019). Consistently, our data revealed that silencing of Ku70 upregulate the level of Bax.…”
Section: Discussionsupporting
confidence: 84%
“…Silencing of Ku70 transcription and translation is known to be more significant than the mitigation of Ku70 acetylation modifications, indicating a Ku70 dosage-dependent elevation of Bax in cells (Ding et al 2021;Wang et al 2020). The Bax then leads to the release of pro-apototic factors, such as Cyt-c from the mitochondria and the activation of the caspases, resulting in the initiation of the intrinsic pathway of apoptosis (Shailender et al 2020;Wang et al 2019). Consistently, our data revealed that silencing of Ku70 upregulate the level of Bax.…”
Section: Discussionsupporting
confidence: 84%
“…The results showed that compared with the non‐irradiation group, the cells in the irradiation group were all blocked in the G2/M phase; Compared with the irradiation control group, 20 and 40 μg/mL tCQA significantly inhibited the effect of 8Gy IR on G2/M phase of blockade (Figure 2D,E). According to reports, G2/M phase is regulated by CDK1‐cyclin B1 complex 23 ; CDK1 activation is a necessary condition for G2 phase to enter M phase; Thr‐161 phosphorylation can activate CDK1 24,25 ; After the complex formed by cyclin B1 and CDK1 is activated, the cell cycle enters M phase from G2 phase; Radiation injury is often accompanied by decreased expression of cyclin B1 25–27 . Western blot showed that 8Gy IR degraded cyclin B1 and inhibited CDK1 activation; however, tCQA could significantly increase the protein levels of cyclin B1 and CDK1 (pThr‐161; Figure 2F).…”
Section: Resultsmentioning
confidence: 99%
“…RNA interference (RNAi) has become one of the powerful tools in recent times to suppress the expression of speci c gene of interest [17][18], as a therapeutic option in disease management [19][20][21][22], as cancer treatment [23][24][25] and for understanding regulatory function of a gene by dsRNA molecules [26]. Suppression of gene expression achieved by cleavage of dsRNA molecules by ribonuclease protein (Dicer) followed by loading of siRNA molecules into RISC (RNA induced silencing complex) and then, guide strand of the siRNA molecule would guide the RISC towards the target mRNA sequence complementary with the siRNA for cleavage of target mRNA [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%